New Chemical Weapons Destruction Technologies as the Key to Successful Completion of Chemical Weapons Disarmament Process - V. P. Kapashin; V. G. Mandych; I. N. Isaev; I. V. Kovalenko; V. L. Veriga (Вестник войск РХБ защиты, 2022)
The fulfillment of international obligations of the Russian Federation under the Convention on the Prohibition of the Development, Production, Stockpiling and Use of Chemical Weapons and on Their Destruction required the development and the creation of safe innovative industrial technologies and facilities for the destruction of chemical weapons. The purpose of this work is to give brief characteristics of the technologies for the destruction of chemical weapons developed and commercially implemented at various facilities. The destruction of chemical weapons was carried out at seven facilities specially designed and built for this purpose. These facilities were located in six regions of the country. The choice of technologies for the destruction (utilization) of chemical weapons was carried out on a competitive basis in the period from 1992 to 1995. The priority was given to the so-called two-stage technology. At the first stage, the toxic chemicals were extracted from the munitions or the containers and detoxified chemically in «soft» controlled conditions. Then the empty munitions were degassed. At the second stage, thermal neutralization or bituminization of the reaction masses was carried out with their subsequent burial. The two-stage technology for the destruction of mustard and mustard-lewisite mixtures was based on the interaction of toxic chemicals with an 80 ± 5% aqueous solution of monoethanolamine, which was supplied into the reactor at a temperature of 60–80 °C in the ratio toxic chemical: degassing formulation - 1:1.2 according to mass. The detoxification process was considered completed if the content of toxic chemicals in the reaction mass did not exceed 3,2×10-3%. To destroy lewisite, a «short scheme» in a jet-type reactor was implemented. The mixing of the initial reagents, lewisite and 20% alkali solution, was carried out using a nozzle of a special design, where lewisite was swirled with a special device (swirler) and supplied into the reactor. The first stage of the destruction of V-gases was carried out in munitions cases. The munitions were considered as chemical reactors. The process of detoxification of V-gases was considered completed when the residual content of toxic chemicals was at the level of 5×10-4%, and the reaction mass was delivered for thermal neutralization (second stage). In total, 39966,588 tons of toxic chemicals were destroyed. The whole number of destroyed containers with agents and chemical munitions amounted to 4,158,456 units. On September 27, 2017, the last chemical weapon was destroyed at the Kizner chemical weapons destruction facility, thus completing the process of complete destruction of chemical weapons stockpiles in the Russian Federation.